Symbolism of Sacred Art in Water Conduits - Khanal, Sandhya (Nepalese Culture, 2024)
Nepal is a country with abundance of traditional art, architecture and culture. Almost every monument comprises faith, belief, devotion and sacredness which are initiated to be expressed through symbolic representation. Historicity of water conduit of Kathmandu valley can be traced back to early Cristian Era. They were installed to fulfill basic need of water. Flowing water is compared to goddess Ganga. Thus, every water conduit is equated to goddess Ganga with depiction of a crocodile, her vehicle. Cent percent water conduits of the valley consists of sculptural art associated to Hindu or Buddhist deities and a few with architectural monuments. It also comprises sculptural art of several creatures as; serpent, fish, frog, chameleon, mongoose. These deities, monuments and creatures are found to be a symbolic expression of theme associated with religious belief and faith. In this context, finding out the theme of an art expressed in a water conduit, chief feature of sacred sculptural art of water conduits and symbolic representation of sculptural art of water conduits of Kathmandu valley have been focused as an objective of this research. This qualitative research is based upon historical fact. Thus, the facts are collected from historical monuments through survey, interview, collection of photographs and are analyzed in a descriptive way. Related literary sources have been consulted as a secondary source. From several references, it is to be considered that water conduits of the valley have been basically set up for social and religious utility with installation of several deities according to their faith. Art of each conduit as well as image portrays specific features belong to related historical age. Besides this, each sculptural art depicted on the conduit conveys symbolism of goddess Ganga and several pilgrimages composed within a precise pious abode.